Antibiotic Resistance, Virulence Genes, and Molecular Diversity of Clinical Klebsiella pneumoniae Isolates from Patients of District Hospital in Central Poland - Barbara Kot; Małgorzata Witeska; Piotr Szweda; Małgorzata Piechota; Elżbieta Kondera; Elżbieta Horoszewicz; Izabela Balak; Ahmer Bin Hafeez; Alicja Synowiec (Pathogens, 2025)
In hospital environments, pathogenic bacteria spread easily and acquire virulence and antibiotic resistance genes. The aim of the study was an evaluation of the genetic diversity of 109 K. pneumoniae isolates recovered from patients of a district hospital in central Poland. The frequencies of genes coding for β-lactamases, efflux pumps, and virulence factors were determined. Genotyping of the isolates was performed with ERIC (Enterobacterial Repetitive Intergenic Consensus) and REP (Repetitive Element Sequence Based) PCR techniques, with 21 and 19 genotypes being identified, respectively. The blaSHV-1 (92.7%), blaCTX-M group 1 (83.5%), blaTEM-1 (28.4%), blaNDM-1 (16.5%), blaVEB-1 (11.0%), blaCTX-M group 9 (3.7%), blaKPC (1.8%), blaIMP, blaOXA-48, blaCTX-M group 2, blaCTX-M groups 8, and 25/26 (0% each) and efflux pumps: AcrAB (100%), tolC (93.6%), and mdtk (60.5%), and virulence genes coding: urease subunit ureA (94.5%) endotoxins wabG (92.7%) and uge (64.2%), and siderophore iucB (3.7%) were detected. The blaSHV-1, blaCTX-M group 1, mdtk, tolC, AcrAB (16.5%); blaSHV-1, blaCTX-M group 1, tolC, AcrAB (15.6%), and blaSHV-1, blaCTX-M group 1, blaNDM-1, mdtk, tolC, AcrAB (11.9%) were the most common resistance patterns. The distribution of resistance and virulence genes varied more between hospital wards than between different clinical materials. Hospital’s antibiotic-resistant and virulent K. pneumoniae, able to spread among humans, animals, and in the environment, pose a significant threat to public health.